2011
DOI: 10.1007/s12011-011-9188-5
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Physical Exercise on the Serum Iron Profile in Spontaneously Hypertensive Rats

Abstract: The purpose of this study was to evaluate the profile of serum iron in spontaneously hypertensive rats after an aerobic physical exercise. To accomplish this, 12 normotensive Wistar rats and 12 spontaneously hypertensive rats were distributed into "physical exercise" and "no physical exercise" groups. The animals in the physical exercise group underwent to an aerobic exercise for a total of 4 weeks. Blood was collected for the analysis of iron. Our results indicate that rats of the physical exercise group had … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…8 The effects of the hypertensive state and anti-hypertensive treatments on iron metabolism have not been rigorously explored. 29 In the present study, we found significantly lower levels of serum and liver iron in SHRs compared with WKY rats, indicating that hypertension is associated with systemic lowiron status. These results are consistent with a previous study showing that serum iron levels were decreased in SHRs compared with normotensive animals.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…8 The effects of the hypertensive state and anti-hypertensive treatments on iron metabolism have not been rigorously explored. 29 In the present study, we found significantly lower levels of serum and liver iron in SHRs compared with WKY rats, indicating that hypertension is associated with systemic lowiron status. These results are consistent with a previous study showing that serum iron levels were decreased in SHRs compared with normotensive animals.…”
Section: Discussionsupporting
confidence: 55%
“…Essential hypertension is a multifactorial disease that accounts for 95% of hypertensive patients 8 . The effects of the hypertensive state and anti‐hypertensive treatments on iron metabolism have not been rigorously explored 29 . In the present study, we found significantly lower levels of serum and liver iron in SHRs compared with WKY rats, indicating that hypertension is associated with systemic low‐iron status.…”
Section: Discussionmentioning
confidence: 48%
“…In the present study, we observed that the rats in the SHR group had a higher serum iron concentration, and a lower transferrin concentration, compared to the WK group. Other researchers have also observed higher serum iron concentrations in SHRs compared to WK rats (Frank et al, 2012). One study (Ward et al, 2014) suggested that some patients with RLS may have normal serum iron concentration; however, at the central level the concentration may be low.…”
Section: Resultsmentioning
confidence: 96%